Development of children's social care attitudes through advocacy activities - Dwi Retnani Srinarwati; Akhmad Qomaru Zaman; Eka Safitri Utami (JPPI (Jurnal Penelitian Pendidikan Indonesia), 2023)
This research was conducted against the background of the phenomenon of declining social behavior in society and the problems it causes. The purpose of this study is to analyze and describe the development of children's social behavioral attitudes through advocacy activities. The research approach used is descriptive qualitative. The subjects of this study were children aged 8-12 years in Taman District, Sidoarjo. The data collection techniques used are observation, interviews, and documentation. The results showed that advocacy activities can develop children's social care attitudes towards various social issues that develop in the community. These issues include the environment, social justice, education, and health. Participation in advocacy activities illustrates cooperation in the form of collaboration between children with each other. They learn to cooperate in achieving goals. The role of advocacy institutions is initiation, planning, mobilizing resources, implementing, monitoring, and evaluating.